NEONATAL OUTCOMES OF INTRAUTERINE GROWTH RESTRICTION CASES FROM 37 WEEKS AT HANOI OBSTETRICS AND GYNECOLOGY HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate neonatal outcomes in cases of fetal growth restriction from 37 weeks of gestation at Hanoi Obstetrics and Gynecology Hospital.Objects and Methods: A prospective cross-sectional descriptive study was conducted on 139 pregnant women at ≥37 weeks of gestation diagnosed with fetal growth restriction. Neonatal outcomes were followed up and evaluated in infants born to mothers admitted for management and pregnancy termination at Hanoi Obstetrics and Gynecology Hospital.Results: Increasing gestational age was associated with a lower birth weight percentile (p < 0.05). The mean birth weight was 2320 ± 153.2 g. One neonatal death was recorded (0.7%), occurring in the group with a birth weight percentile below the 3rd percentile. The proportion of neonates with a 1-minute Apgar score
Keywords: Fetal growth restriction; neonatal outcomes